Waqf et gestion des bains publics à Alger durant la période ottomane (xvie-xixe siècle) - Nabila Cherif-Seffadj (Revue des Mondes Musulmans et de la Méditerranée)
Considering their high economic rentability, the baths of Algiers, during Ottoman period, were most often constituted in property waqf to the advantage of religious, charitable or public utility institutions. The archives of the Ottoman administration (registers of Baylîk and documents of the juridical courts) give informations about various aspects concerning their management and the practice of the waqf within the foundations to which they are transferred.